Combining Ability Analysis In Rice (Oryza Sativa L.) - Akter, A; Hasan, MJ; Begum, H; Kulsum, MU; Hossain, MK (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Twenty hybrids were produced using five CMS lines viz., BRRI3A, BRRI9A, IR73328A, BRRI10A and IR78355A and four restorers viz., BRRI12R, BRRI13R, BRRI14R and BRRI15R following line x tester mating design to find out the best combination (s) in respect of their combining ability effects among the parents and hybrids at BRRI, Gazipur, Bangladesh from July 2008 to May 2009. Data were recorded from yield and yield contributing agronomic characters each entry through out the replications and mean values were subjected to line x tester analysis. The genotypes were found highly significant for all the traits which indicated that the treatments used in this study were significantly varied from each other. After the partitioning of mean sums of squares (MSS) of the treatments into parent, cross and parent vs cross. They were found highly significant except yield per plant for parent, panicle weight for crosses and leaf area index for parent vs cross. The ratio of GCA and SCA variances were found less than unity for all the characters except plant height, days to maturity and panicles per square meter. The relative contribution of line, tester and combinations of line x tester interaction of ten characters were calculated and found that panicle weight contributed the highest (69.53%) followed by thousand grain weight (63.62%), yield per plant (54.76%), panicle per meter square 51.52% in their hybrids. IR73328A was identified as good general combiner for shorter plant height (-6.09) and panicle per square meter (16.92). BRRI10A and IR78355A produced significant positive GCA for yield per plant which could be regarded as good general combiner for higher grain yield. Six hybrid combinations were found with significant and positive SCA effect of which the highest value was obtained from BRRI3A/BRRI14R (2.46) followed by IR73328A/BRRI13R (2.23) for yield per plant. Key words: Line × tester; GCA; SCA; rice DOI: http://dx.doi.org/10.3329/bjpbg.v23i2.9319 Bangladesh J. Pl. Breed. Genet., 23(2): 7-13, 2010